Acute Kinematic and Kinetic Adaptations to Wearable Resistance During Sprint Acceleration. Issue 5 (May 2017) - Macadam, Paul; Simperingham, Kim D.; Cronin, John B.
Abstract : Abstract: Macadam, P, Simperingham, KD, and Cronin, JB. Acute kinematic and kinetic adaptations to wearable resistance during sprint acceleration. J Strength Cond Res 31(5): 1297–1304, 2017—Wearable resistance (WR) in the form of weighted vests and shorts enables movement-specific sprint running to be performed under load. The purpose of this study was to determine the acute changes in kinematics and kinetics when an additional load equivalent to 3% body mass (BM) was attached to the anterior or posterior surface of the lower limbs during sprint running. Nineteen male rugby athletes (age: 19.7 ± 2.3 years; body mass: 96.1 ± 16.5 kg; height: 181 ± 6.5 cm) volunteered to participate in the study. Subjects performed six 20 m sprints in a randomized fashion wearing no resistance or 3%BM affixed to the anterior (quadriceps and tibialis anterior) or posterior (hamstring and gastrocnemius) surface of the lower limbs (2 sprints per condition). Optojump and radar were used to quantify sprint times, horizontal velocity, contact and flight times, and step length and frequency. A repeated measures analysis of variance with post hoc contrasts was used to determine differences ( p ⩽ 0.05) between conditions. No significant differences were found between the anterior and posterior WR conditions in any of the variables of interest. There was no significant change in sprint times over the initial 10 m, however, the 10–20 m split times were significantly slower (−2.2 to −2.9%) for the WR conditions compared with the unloaded sprints. A significant change in the relative force–velocity ( F – v ) slope (−10.5 to −10.9%) and theoretical maximum velocity ( V 0 ) (−5.4 to −6.5%) was found, whereas a nonsignificant increase in theoretical maximum force ( F 0 ) (4.9–5.2%) occurred. Wearable resistance of 3%BM may be a suitable training modality to enhance sprint acceleration performance by overloading the athlete without negatively affecting sprint running technique.